Informal Sector Taxation: A Qualitative Analysis Of The Experience Of The Urban Informal Operators In Rustenburg, North West Province - Mokgatlhe, Amogelang (College of Accounting, 2024)
Most developing countries, including South Africa, consist of large informal sectors that are vital to their economies. In South Africa, the informal sector plays a significant role in both production and employment. Government revenue and spending are affected by informality. South Africa faces evident revenue and fiscal pressures. The Davis Tax Committee has highlighted the necessity of increasing tax compliance and broadening the tax base to reduce revenue shortfalls. This research is informed by the informal sector's low tax revenue contribution, that contrasts with its continuing expansion and significant GDP contribution. This study is also motivated by the scarcity of research focusing on informal sector taxation in South Africa. The research explores the perceptions of the informal operators to obtain an understanding of their tax compliance behaviour and attitude. The study employed semi-structured interviews with ten informal operators in Rustenburg in the North West Province of South Africa to obtain an in-depth understanding of their tax compliance behaviour. The research found that the informal operators generally possess a positive willingness to comply with taxation. It also revealed challenges faced by informal operators regarding tax compliance. Recommendations were made towards improving tax collection in the informal sector based on the observed tax compliance behaviour of the participating informal operators and the challenges they faced as revealed by the study.